External Beam Irradiation Preferentially Inhibits the Endochondral Pathway of Fracture Healing: A Rat Model. Issue 10 (October 2018) - Wu, Yongren; Hanna, E. Lex; Holmes, Robert E.; Lin, Zilan; Chiaramonti, Alexander M.; Reeves, Russell A.; McDonald, Daniel G.; Vanek, Kenneth N.; Barfield, William R.; Yao, Hai; Pellegrini, Vincent D.
Abstract: Background: External beam irradiation is an accepted treatment for skeletal malignancies. Radiation acts on both cancerous and normal cells and, depending on the balance of these effects, may promote or impair bone healing after pathologic fracture. Previous studies suggest an adverse effect of radiation on endochondral ossification, but the existence of differential effects of radiation on the two distinct bone healing pathways is unknown. Questions/purposes: The purpose of this study was to investigate the differential effects of external beam irradiation on endochondral compared with intramembranous ossification with intramedullary nail and plate fixation of fractures inducing the two respective osseous healing pathways through assessment of (1) bone biology by histomorphometric analysis of cartilage area and micro-CT volumetric assessment of the calcified callus; and (2) mechanical properties of the healing fracture by four-point bending failure analysis of bending stiffness and strength. Methods: Thirty-six male Sprague-Dawley rats underwent bilateral iatrogenic femur fracture: one side was repaired with an intramedullary nail and the other with compression plating. Three days postoperatively, half (n = 18) received 8-Gray external beam irradiation to each fracture. Rodents were euthanized at 1, 2, and 4 weeks postoperatively (n = 3/group) for quantitative histomorphometry of cartilage area and micro-CT assessment of callus volume. The remaining rodents were euthanized at 3 months (n = 9/group) and subjected to four-point bending tests to assess stiffness and maximum strength. Results: Nailed femurs that were irradiated exhibited a reduction in cartilage area at both 2 weeks (1.08 ± 1.13 mm 2 versus 37.32 ± 19.88 mm 2 ; 95% confidence interval [CI] of the difference, 4.32-68.16 mm 2 ; p = 0.034) and 4 weeks (4.60 ± 3.97 mm 2 versus 39.10 ± 16.28 mm 2 ; 95% CI of the difference, 7.64-61.36 mm 2 ; p = 0.023) compared with nonirradiated fractures. There was also a decrease in the volume ratio of calcified callus at 4 weeks (0.35 ± 0.08 versus 0.51 ± 0.05; 95% CI of the difference, 0.01-0.31; p = 0.042) compared with nonirradiated fractures. By contrast, there was no difference in cartilage area or calcified callus between irradiated and nonirradiated plated femurs. The stiffness (128.84 ± 76.60 N/mm versus 26.99 ± 26.07 N/mm; 95% CI of the difference, 44.67-159.03 N/mm; p = 0.012) and maximum strength (41.44 ± 22.06 N versus 23.75 ± 11.00 N; 95% CI of the difference, 0.27-35.11 N; p = 0.047) of irradiated plated femurs was greater than the irradiated nailed femurs. However, for nonirradiated femurs, the maximum strength of nailed fractures (36.05 ± 17.34 N versus 15.63 ± 5.19 N; 95% CI of the difference, 3.96-36.88 N; p = 0.022) was greater than plated fractures, and there was no difference in stiffness between the nailed and plated fractures. Conclusions: In this model, external beam irradiation was found to preferentially inhibit endochondral over intramembranous ossification with the greatest impairment in healing of radiated fractures repaired with intramedullary nails compared with those fixed with plates. Future work with larger sample sizes might focus on further elucidating the observed differences in mechanical properties. Clinical Relevance: This work suggests that there may be a rationale for compression plating rather than intramedullary nailing of long bone fractures in select circumstances where bony union is desirable, adjunctive radiation treatment is required, and bone stock is sufficient for plate and screw fixation.